The Development Of Batik Babon Angrem at Traditional Birth Ceremonies in Central Java - Nimas Elizabeth; Theresia Widyastuti (Pusat Penerbitan LP2MPP ISI Denpasar, 2021)
The life cycle ceremonies that symbolize the human journey are all found in traditional Javanese batik, because in batik there is a symbol or meaning of life. At the age of 7 months of pregnancy, Javanese people usually hold a ceremony called mitoni, this ceremony is equipped with various ubo rampe, one of which is Babon Angrem batik. Changes in times including changes in cultural actors have caused many shifts in customs. This traditional ceremony began to be abandoned or reduced in terms of its completeness related to economic factors. As individuals in this millennial era, there is a change in the benefits of having traditional ceremonies seen from a modern perspective. From this problem, the idea emerged to develop one of the mitoni ceremonial equipment in the form of a long cloth with a millennial pattern that still adheres to the existing standard. Batik is one of the assets that can be processed as a creative industry strength. By reprocessing and redefining the existing traditional motifs seen through today's modern glasses, without destroying the meaning in them while maintaining their originality. This design will certainly answer the problems of the world of batik and tradition, with the aim of continuing batik to the present generation according to their style. The textile product produced is in the form of batik cloth with a development pattern from the Babon Angrem batik motif as an innovation from its visuals. The Babon Angrem batik motif, which is designed in a contemporary way, displays bright and warm colors that convey the impression of mother's love in accordance with the philosophical meaning of the Motif of Babon Angrem. the motif components contained in Babon Angrem batik such as Babons or hen facing each other, hen laying eggs, ukel motifs that adorn all repetitions of Babon motifs, and ceceg which complete the background of this batik.